The top 100 most cited articles in the last two decades of atopic dermatitis: A bibliometric analysis - Zhang, Lishan; Hou, Yibo; Sun, Jinlyu; Zeng, Yueping (Frontiers in Immunology, 2022)
Background: Atopic dermatitis is the leading cause of skin-related disease burden worldwide, affecting a large percentage of the population. Bibliometrics is the statistical analysis of academic literature in a certain field. Objectives: We aimed to perform the latest bibliometric analysis of atopic dermatitis literature. Methods: We searched the Web of Science database on 29 Nov 2021. We used the keywords “atopic dermatitis,” “atopic eczema,” and “eczema” for our search. All items published between 2001 and 2021 were included. The top 100 most cited articles were identified and analyzed. Results: Our study provided a detailed bibliometric analysis of the top 100 most cited articles on atopic dermatitis. These articles were published between 2002 and 2019 and were from 15 different countries, mostly in the USA and Germany. Most articles have focused on the pathogenesis of AD and treatment. The Journal of Allergy and Clinical Immunology made the greatest contribution to the top 100 list, with 28 articles. The most cited article originated from Lancet. The highest number of citations was seen in 2006, with 9220 citations, while the highest number of publications was seen in 2006 with 12 publications. Conclusions: Our study aims to provide physicians and researchers with a historical perspective for the scientific progress of atopic dermatitis, and help clinicians effectively obtain useful articles that have a significant impact on the field of atopic dermatitis.